Flood-Irrigated Grain Sorghum Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication projects a budget that reflects expected income and costs based on flood-irrigated grain sorghum production in western Kansas.
MF580_2003_10
Keywords: MF580; Economics; Crops; MF